Changes and continuities in gambling careers during the COVID-19 pandemic: a longitudinal qualitative study of regular sports bettors in Britain - Ashley Brown; Craig Donnachie; Nathan Critchlow; Christopher Bunn; Fiona Dobbie; Cindy M Gray; Richard Purves; Gerda Reith; Heather Wardle; Kate Hunt (BMC Public Health)
Abstract Background To explore continuities and changes in gambling behaviour during the COVID-19 pandemic and the factors that influenced these among a sample of regular sports bettors. Methods A longitudinal qualitative study using in-depth interviews. Sixteen sports bettors living in Britain took part in the first interviews in July-November 2020, and 13 in the follow-up interviews in March-September 2021. Results Individual patterns of gambling were episodic: it was common for gambling to increase during some periods of the pandemic and to decrease during others, reflecting the dynamic and (often) challenging circumstances which people were living through at the time. Changes and continuities in gambling during the pandemic were influenced by a range of factors which we have grouped into two main themes relating to ‘gambling and the sports landscape’ and ‘disruption to day-to-day life’. It was common for a constellation of factors to influence gambling behaviour rather than a single factor. These constellations of factors varied from person to person and at different times during the pandemic. Conclusions Findings of the present study are consistent with earlier literature examining gambling careers before the advent of COVID-19 showing that gambling trajectories are non-linear. Our research suggests that ‘typical’ patterns of gambling behaviour (e.g. being episodic), and the broader known risk and protective factors within individuals, families, communities and societies have been amplified during the pandemic. Findings highlight the adaptability of the gambling industry to continue to reach consumers through product offerings and marketing even in a period of unprecedented restrictions on supply, and show the potential resulting harms of these actions among gamblers at risk of experiencing gambling problems. Taken together, findings from this study provide important new insights relevant to discussions about gambling regulation, and support calls for multifaceted and comprehensive policy, regulatory, and treatment approaches, to minimise gambling-related harms.